Engrafted NSG-SGM3 humanized mice spontaneously produce human immunoglobulins including IgE - Lin, Erica V.; Krier-Burris, Rebecca A.; Sokol, Kristina A.; Arce, Betania; Vilela, Natalia M.; Hamilton, Robert G.; Bochner, Bruce S.; Dispenza, Melanie C. (Frontiers in Immunology, 2025)
NSG-SGM3 humanized mouse models are well-suited for studying human immune physiology but are technically challenging and expensive. We previously characterized a simplified NSG-SGM3 mouse, engrafted with human donor CD34+ hematopoietic stem cells without receiving prior bone marrow ablation or human secondary lymphoid tissue implantation, that still retains human mast cell- and basophil-dependent passive anaphylaxis responses. Its capacities for human antibody production and human B cell maturation, however, remain unknown. Here, we show that NSG-SGM3 mice engrafted without prior marrow ablation spontaneously produce all human antibodies, including IgE, without deliberate sensitization. These human IgE antibodies are polyclonal with unexpected specificities to diverse allergens, such as millet, egg, and wasp venom, that are otherwise absent from the mouse diet or housing environments. Furthermore, human CD138+ CD27+ plasma cell and CD20+ CD27+ memory B cell populations can be expanded from naïve engrafted NSG-SGM3 splenocytes in response to human CD40L and IL-4 cytokine stimulation ex vivo. Engrafted NSG-SGM3 mice, but not non-engrafted controls, also exhibit dose-dependent passive systemic anaphylaxis responses when challenged with goat anti-human IgE. In contrast, no anaphylaxis responses were observed in humanized NSG-SGM3 mice challenged with select food allergens. Together, our results demonstrate that engrafted NSG-SGM3 mice without prior ablation spontaneously produce abundant functional human antibodies, including polyclonal IgE that can facilitate anaphylaxis. These mice also unexpectedly possess the upstream capacity to support human B cell maturation into antibody-producing plasma cells and memory B cells. Our simpler humanized NSG-SGM3 model therefore reveals novel insights into dynamics of human B cell maturation, homing, and differentiation that facilitate the generation of a basal, functional, polyclonal IgE repertoire without deliberate sensitization.